COUP-TFI: an intrinsic factor for early regionalization of the neocortex - Chengji J. Zhou; Sophia Y. Tsai; Ming‐Jer Tsai (2001)
Regionalization of the cerebral cortex is thought to involve two phases: an early regionalization phase and a later refinement phase. It has been shown that early regionalization of the neocortex does not require thalamic inputs and is regulated by intrinsic factors. Recently, two such intrinsic factors, Pax6 and Emx2 , have been identified. In this study, we identified COUP-TFI as a regulatory factor for early neocortical regionalization. The spatial and temporal expression pattern of COUP-TFI suggested a role in specification of the neocortex and in maintaining cortical identity. Altered region-specific expression of marker genes in the cortex as well as miswired area-specific connections between the cortex and the thalamus in COUP-TFI null mice indicate COUP-TFI plays a critical role in regulating early regionalization. Our results substantiate that COUP-TFI , an intrinsic factor, may work in concert with Pax6 and Emx2 to specify neocortical identity.